Activation of the Akt–CREB signalling axis by a proline‐rich heptapeptide confers resistance to stress‐induced cell death and inflammation. Issue 4 (16th May 2017) - Herkel, Johannes; Schrader, Jörg; Erez, Neta; Lohse, Ansgar W.; Cohen, Irun R.
Summary: Cell stress of various kinds can lead to the induction of cell death and a damaging inflammatory response. Hence, a goal of therapeutic cell‐stress management is to develop agents that might effectively regulate undesirable cell death and inflammation. To that end, we developed a synthetic peptide of seven amino acids based on structural mimicry to a functional domain of p53, a key factor in the responses of cells to stressful stimuli. This heptapeptide, which we term Stressin‐1, was found to inhibit both cell death and the secretion of inflammatory mediators by various cell types in response to different stressful agents in vitro . The combined anti‐inflammatory and anti‐apoptotic activities of Stressin‐1 were associated with a cellular signalling cascade that induced activation of Akt kinase and activation of the cAMP response element‐binding protein (CREB) transcription factor. These immediate signalling events led to the inhibition of the signal transducer and activator of transcription and nuclear factor‐ κ B pathways 24 hr later. Unexpectedly, we found no evidence for a direct involvement of p53 in the effects produced by Stressin‐1. Intraperitoneal administration of 100 μg of Stressin‐1 to lethally irradiated mice significantly protected them from death. These findings show that activating the Akt–CREB axis with Stressin‐1 can counteract some of the undesirable effects of various cell stresses. Stressin‐1 may have clinical usefulness. Abstract : We describe a peptide that has anti‐inflammatory and anti‐apoptotic activity through its ability to activate the Akt pathway in immune cells leading to inhibition of the STAT and NF‐κB pathways.